Cool-Shot Technique to Protect Spinal Cord during Thoracoabdominal Aortic Replacement - Yamamoto, Taira; Endo, Daisuke; Yokoyama, Yasutaka; Tabata, Minoru (The Thoracic and Cardiovascular Surgeon, 2024)
Deep hypothermia helps protect the spinal cord, but is invasive. Here, we present a method to avoid reperfusion injury by selectively circulating cold blood under high pressure to the intercostal artery during reperfusion after intercostal artery reconstruction. Of the 23 patients who underwent thoracoabdominal aortic aneurysm open repair, one died. The motor evoked potential disappeared during aortic clamping in nine patients. Six patients recovered completely from aortic clamping release, two showed recovery >50% and one achieved full recovery 3 months later. Permanent motor impairment did not occur. This method could prevent reperfusion injury and paraplegia following thoracoabdominal aortic aneurysm surgery.
Keywords: thoracoabdominal aortic aneurysm; cool-shot technique; spinal cord protection; reperfusion injury